Astyanax jordanensis (Ostariophysi: Characidae), a new species from the rio Iguaçu basin, Paraná, Brazil - Héctor S. Vera Alcaraz; Carla S. Pavanelli; Vinicius A. Bertaco (Neotropical Ichthyology)
Astyanax jordanensis, new species, is described from the rio Jacu and rio das Torres, both tributaries to the lower rio Jordão, in the rio Iguaçu basin, Paraná, Brazil. The new species is a member of the A. scabripinnis species complex. Astyanax jordanensis differs from its congeners by several meristic and morphometric characters. Mature males possess bony hooks in the dorsal, pectoral, pelvic, and anal fins, and mature females have a few small bony hooks on the first rays of the anal fin. The presence of these bony hooks in females and the endemism of the ichthyofauna in the rio Jordão are discussed.